Diagnostic performance of coronary artery disease prediction model (CAD-score system) based on phonocardiogram: a systematic review and meta-analysis - Pramudyo, Miftah; Faried, Ahmad; Akbar, Mohammad Rizki; Hakim, Dzulfikar Djalil Lukmanaul; Setiawan, Agung Wahyu; Kamarullah, William (Frontiers in Cardiovascular Medicine, 2025)
IntroductionPre-test probability stratification of individuals with suspected obstructive coronary artery disease (CAD) has remained suboptimal for many years. Consequently, the majority of diagnostic tests used to rule out CAD exhibit normal results. An acoustic device capable of measuring micro bruits caused by stenosis-induced turbulence in the coronary circulation has showcased potential for stratifying CAD. The aim of this meta-analysis was to investigate the conceivable diagnostic value of phonocardiogram (PCG) in detecting the presence of CAD.MethodsWe conducted a comprehensive search of PubMed, EuropePMC, and ScienceDirect for articles published through January 2025. Studies were eligible if they assessed the accuracy of PCG using the CADScor® system in predicting CAD and provided enough data to construct a 2 × 2 contingency table.ResultsA total of 4 studies involving 4,050 patients were included for the final analysis. The pooled sensitivity and specificity were 87% (95% CI, 80%–92%) and 35% (95% CI, 21%–52%), respectively. The pooled positive likelihood ratio (PLR) was 1.34 (95% CI, 1.09–1.64) and the pooled negative likelihood ratio (NLR) was 0.37 (95% CI, 0.25–0.55). The area under the receiver operating characteristic curve (AUC) was 0.79 (95% CI, 0.75–0.82) in predicting CAD. Fagan's nomogram showed that the posterior probability of PCG with the CADScor® system for the detection of CAD was 19% when the CAD-score was above the cut-off value, and 6% in those with CAD-score below the cut-off value.ConclusionPhonocardiography shows promise as a rule-out tool for patients with suspected CAD.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024550526, PROSPERO CRD42024550526.